2010
DOI: 10.1007/s11999-009-0995-3
|View full text |Cite
|
Sign up to set email alerts
|

Which is the Best Method to Determine the Patellar Height in Children and Adolescents?

Abstract: Patellar height is associated with various clinical syndromes. We asked which of three methods was the most appropriate for measuring patellar height for different age groups in terms of applicability, validity, and reliability. We evaluated 108 children and adolescents with available MR images and lateral knee radiographs using Insall-Salvati (IS), Blackburne-Peel, and Koshino-Sugimoto (KS) methods. Subjects were divided equally into three age groups (A, 5-10.9 years; B, 11-12.9 years; C, 13-18 years). The ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 28 publications
4
49
0
1
Order By: Relevance
“…[33][34][35][36][37] The Blackburne-Peel and Caton-Deschamps indices assess the patellar height in relation to the tibial plateau and are considered to be more reliable in children compared with the Insall-Salvati index, which is dependent on the ossification of the tibial tubercle. When used in children or adolescents, one has to account for growth and ossification pattern around the knee and their influence on these indices.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36][37] The Blackburne-Peel and Caton-Deschamps indices assess the patellar height in relation to the tibial plateau and are considered to be more reliable in children compared with the Insall-Salvati index, which is dependent on the ossification of the tibial tubercle. When used in children or adolescents, one has to account for growth and ossification pattern around the knee and their influence on these indices.…”
Section: Discussionmentioning
confidence: 99%
“…All radiographic images were digitally acquired using a picture archiving and communication system (PACS; Impax, Agfa, Antwerp, Belgium), and assessments were subsequently carried out using the PACS software. A previous report demonstrated that the Insall-Salvati (IS) 12) and the Koshino-Sugimoto (KS) 13) methods have reasonable reliability and validity with respect to depicting the patellar height in children and adolescents, 14) and therefore, IS and KS ratios were used to determine the patellar height. On lateral knee radiographs, the IS method was used to measure patellar tendon length relative to patellar bone length, and the KS method was to measure the ratio of the distance between the proximal tibial physis and the center of the patella to the distance between the distal femoral physis and the proximal tibial physis.…”
Section: Methodsmentioning
confidence: 99%
“…As the Insall-Salvati method has been shown to be the most reliable, it was used to measure patella alta [11]. As the Insall-Salvati method has been shown to be the most reliable, it was used to measure patella alta [11].…”
Section: Case Reportmentioning
confidence: 99%